Membaca Sandur Bojonegoro dan Sandur Tuban - J. Catur Wibono; Trisno Tri Susilowati; M. Ali As’ad (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2009)
Reading Bojonegoro and Tuban’s Sandur Performances. Sandur performance is a form of social and culturalactivities of agrarian society. This study focuses on the difference between Bojonegoro and Tuban’s Sandurperformances. This performance is a form of expression patterns of thought and feeling into a tangible folk art. Itwill compare the themes of the stories, the actors, makeup and fashion, properties, music accompaniment, stages,time of performances and audiences. Comparative study of aesthetic forms an important aspect in order to analyze atraditional theater. Based on the research concluded that Sandur performance is one way to present the creative ideaswith aesthetic value. Performing of Sandur also has a complexity of meaning contained therein.